Role of Consultancy in Engineering Education - Nalina, V.; Jayarekha, P. (Journal of Engineering Education Transformations, 2015)
Consultancy by an engineering faculty member of an institution undertakes consulting assignments to provide professional or technical solutions to specific fields. Consulting is providing an opportunity for the engineering faculty to share their insights for the real world problems. It is a dynamic learning process with respect to students and faculty as it increases the teaching and research activities. In this paper we discuss about the need for consultancy in engineering education with faculty contribution towards consultancy and advantages of consultancy to institutions. Balance the workload of the faculty consulting with the responsibilities of academics defined by the universities.